Functional Role of Adult Hippocampal Neurogenesis as a Therapeutic Strategy for Mental Disorders - Heechul Jun; Syed Mohammed Qasim Hussaini; Michael J. Rigby; Mi-Hyeon Jang (Neural Plasticity)
Adult neurogenesis, the process of generating new neurons from neural stem cells, plays significant roles in synaptic plasticity, memory, and mood regulation. In the mammalian brain, it continues to occur well into adulthood in discrete regions, namely, the hippocampus and olfactory bulb. During the past decade, significant progress has been made in understanding the mechanisms regulating adult hippocampal neurogenesis and its role in the etiology of mental disorders. In addition, adult hippocampal neurogenesis is highly correlated with the remission of the antidepressant effect. In this paper, we discuss three major psychiatric disorders, depression, schizophrenia, and drug addiction, in light of preclinical evidence used in establishing the neurobiological significance of adult neurogenesis. We interpret the significance of these results and pose questions that remain unanswered. Potential treatments which include electroconvulsive therapy, deep brain stimulation, chemical antidepressants, and exercise therapy are discussed. While consensus lacks on specific mechanisms, we highlight evidence which indicates that these treatments may function via an increase in neural progenitor proliferation and changes to the hippocampal circuitry. Establishing a significant role of adult neurogenesis in the pathogenicity of psychiatric disorders may hold the key to potential strategies toward effective treatment.